Organic acidurias in adults: late complications and management. Issue 5 (15th January 2018) - Tuncel, Ali Tunç; Boy, Nikolas; Morath, Marina A.; Hörster, Friederike; Mütze, Ulrike; Kölker, Stefan
Abstract: Organic acidurias (synonym, organic acid disorders, OADs) are a heterogenous group of inherited metabolic diseases delineated with the implementation of gas chromatography/mass spectrometry in metabolic laboratories starting in the 1960s and 1970s. Biochemically, OADs are characterized by accumulation of mono‐, di‐ and/or tricarboxylic acids ("organic acids") and corresponding coenzyme A, carnitine and/or glycine esters, some of which are considered toxic at high concentrations. Clinically, disease onset is variable, however #Affected individuals may already present during the newborn period with life‐threatening acute metabolic crises and acute multi‐organ failure. Tandem mass spectrometry‐based newborn screening programmes, in particular for isovaleric aciduria and glutaric aciduria type 1, have significantly reduced diagnostic delay. Dietary treatment with low protein intake or reduced intake of the precursor amino acid(s), carnitine supplementation, cofactor treatment (in responsive patients) and nonadsorbable antibiotics is commonly used for maintenance treatment. Emergency treatment options with high carbohydrate/glucose intake, pharmacological and extracorporeal detoxification of accumulating toxic metabolites for intensified therapy during threatening episodes exist. Diagnostic and therapeutic measures have improved survival and overall outcome in individuals with OADs. However, it has become increasingly evident that the manifestation of late disease complications cannot be reliably predicted and prevented. Conventional metabolic treatment often fails to prevent irreversible organ dysfunction with increasing age, even if patients are considered to be "metabolically stable". This has challenged our understanding of OADs and has elicited the discussion on optimized therapy, including (early) organ transplantation, and long‐term care.